Experimental investigation of the effect of electrospinning parameters on properties of superhydrophobic PDMS/PMMA membrane and its application in membrane distillation - Ren, Long-Fei; Xia, Fan; Shao, Jiahui; Zhang, Xiaofan; Li, Jun (Desalination, 2017)
Considerable efforts have been devoted to finding economic and simple preparation methods for polydimethylsiloxane (PDMS) superhydrophobic membrane in past decades. This study provides a simple method to electrospin PDMS membrane using poly (methyl methacrylate) (PMMA) as carrier polymer. Effects of PMMA concentration, PDMS/PMMA mass ratio and main parameters of electrospinning process (voltage and injection rate) were investigated to obtain superhydrophobic membrane with high water contact angle (WCA). A highest WCA of 163° could be obtained on the membrane surface fabricated by electrospinning solution containing PDMS: PMMA: tetrahydrofuran (THF): N,N-dimethylformamide (DMF) (mass ratio 1: 1: 8.88: 9.48) under applied voltage of 11kV and injection rate of 0.1mm/min. The superhydrophobic PDMS/PMMA membrane was further applied in membrane distillation process for desalination, and a high permeation flux of 39.61L/m2h and an excellent salt rejection of 99.96% were achieved during long-term MD process (24h). •Superhydrophobic PDMS/PMMA membrane was electrospun successfully with a contact angle of 163°.•Correlations between electrospinning parameters and membrane properties were firstly established.•Membrane surface roughness and beads structure were well-related with membrane hydrophobicity.•The membrane was suitable for MD process (<24h) with membrane flux of 39.61L/m2h and salt rejection of 99.96%.